DESIGN OF ZIS MANAGEMENT INFORMATION SYSTEM USING WATERFALL MODEL - Didih Aditiyawarman; Alif Rizqi Mulyawan (Journal of Telematics and Informatics, 2020)
Basically, the functions of computers are generally used as a medium for storing data and programs in which there are many applications that can facilitate and support a man's work. At the administration of the institution Baitul Maal Pupuk Kujang, data processing about zakat, infaq and sodaqoh (ZIS), reports, and data storage is done manually. Error and inaccuracies of data can be occurring in this case. To help simplify the ZIS management system in that section, program design is the best solution to solve the problems that exist. Data processing is more accurate because of the availability of the form data entry and storage media are centralized in a single database that will make the ZIS management system become more effective and efficient. This aplication program was created with a simple and interactive interface but can process data well and can meet the requirement of the system, so that users can easily use it